Efektivitas Problem Based Learning Berbasis STEAM dengan Pendekatan Labirin terhadap Penguasaan Konsep Kimia Siswa - Rosanna Saragih; Nancy Susianna; Nerru Pranuta Murnaka (PT. Penerbit Tiga Mutiara, 2026)
Twenty-first-century chemistry learning requires conceptual mastery and the ability to apply concepts to real-world problems, while the mole concept is complex because it involves relationships among amount of substance, mass, particles, volume, molarity, and chemical equations, causing students to rely on memorization. This study aimed to analyze the effectiveness of Problem Based Learning (PBL) based on Science, Technology, Engineering, Arts, and Mathematics (STEAM) with the Labyrinth approach on students’ mastery of the mole concept. The study employed a quasi-experimental method with a pretest–posttest control group design involving 60 tenth-grade students, and the data were analyzed using paired-sample t-test, independent-sample t-test, and N-gain. The results showed that the mean conceptual mastery score of the experimental group increased from 25.52 to 62.70, with an N-gain of 0.52, while the control group increased from 31.97 to 57.03, with an N-gain of 0.39, and the difference in improvement between the groups was significant at the 0.05 level. These findings confirm that PBL based on STEAM with the Labyrinth approach is more effective than conventional learning, with its novelty lying in the integration of cognitive, social, and exploratory activities to strengthen students’ mastery of the mole concept actively and meaningfully.